12.4k views
1 vote
Solve the system of equations by substitution and show work.
​​y=−6x+13
y=3x+4

2 Answers

3 votes

Answer:

(1, 7 )

Explanation:

Given the 2 equations

y = - 6x + 13 → (1)

y = 3x + 4 → (2)

Substitute y = 3x + 4 into (1)

3x + 4 = - 6x + 13 ( add 6x to both sides )

9x + 4 = 13 ( subtract 4 from both sides )

9x = 9 ( divide both sides by 9)

x = 1

Substitute x = 1 into (2) for corresponding value of y

y = 3(1) + 4 = 3 + 4 = 7

Solution is (1, 7 )

User Johnny Dollard
by
5.2k points
3 votes

Answer: x= 1 , y = 7

Explanation:

y = -6x + 13 ................. equation 1

y = 3x + 4 ................ equation 2

substitute y = 3x + 4 into equation 1 , then we have

3x + 4 = - 6x + 13

collect the like terms , we have

3x + 6x = 13 - 4

9x = 9

x = 1

substitute x = 1 into equation 2 , we have

y = 3(1) + 4

y = 3 + 4

y = 7

Therefore : x = 1 and y = 7

User Sloganho
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.